THE INFLUENCE OF MACROECONOMIC VARIABLES ON TRADING OF SUKUK NEGARA DURING PANDEMIC: CASE OF INDONESIA - Fadila, Raehan; Herman, Sebastian; Heriyanto, Eri (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2022)
The year 2020 and 2021 became an unprecedented challenge due to the covid pandemic affecting many aspects around the world, including the economy. On the other side, over the past decade has the global Sukuk market become an increasingly prominent funding source for companies, financial institutions, and governments. For handling the pandemic in Indonesia, the Ministry of Finance has repeatedly issued Sukuk Negara. The objective of study is to analyze the short-term and longterm impact of macroeconomic variables on the sukuk trade in Indonesia and to see the impact of these macroeconomic variables on the stability of the Sukuk Negara Trade and the contribution of these variables during the pandemic to the Sukuk Negara. It was found that the exchange rate and inflation have a significant positive effect on the trading of sovereign sukuk in the secondary market. The most variable contribution is sovereign sukuk trade itself, followed by the Exchange rate.